2022
DOI: 10.1242/dev.199637
|View full text |Cite
|
Sign up to set email alerts
|

A constitutively expressed fluorescent ubiquitination-based cell-cycle indicator (FUCCI) in axolotls for studying tissue regeneration

Abstract: Regulation of cell cycle progression is essential for cell proliferation during regeneration following injury. After appendage amputation, the axolotl (Ambystoma mexicanum) regenerates missing structures through an accumulation of proliferating cells known as the blastema. To study cell division during blastema growth, we generated a transgenic line of axolotls that ubiquitously expresses a bicistronic version of the fluorescent, ubiquitination-based cell cycle indicator (FUCCI). We demonstrate near-ubiquitous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…1c), we tested whether the cell cycle was activated prior to competency induction using the new FUCCI transgenic axolotl line, which allows us to visualize the activation of the cell cycle in real-time in vivo. 35 We observed a detectable increase in mitotic cells in the blastema mesenchyme between 5 and 6 days postsurgery (Fig. 2d), indicating that the acquisition of patterning competency correlates with the activation of the cell cycle.…”
Section: Development Of the Competency-alm (Calm) Assaymentioning
confidence: 71%
See 2 more Smart Citations
“…1c), we tested whether the cell cycle was activated prior to competency induction using the new FUCCI transgenic axolotl line, which allows us to visualize the activation of the cell cycle in real-time in vivo. 35 We observed a detectable increase in mitotic cells in the blastema mesenchyme between 5 and 6 days postsurgery (Fig. 2d), indicating that the acquisition of patterning competency correlates with the activation of the cell cycle.…”
Section: Development Of the Competency-alm (Calm) Assaymentioning
confidence: 71%
“…This analysis also identi ed pathways related to the cell cycle and DNA replication as targets downstream of FGF/BMP signaling. Using the FUCCI transgenic axolotl, 35 we found that the activation of the cell cycle in the blastema mesenchyme correlates with the window of patterning competency establishment (Fig. 2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Salamanders are excellent vertebrate models to apply novel tools to study cell biological aspects of regeneration. For example, the recent development of axolotl Fucci lines independently by both Duerr et al, as well as Cura Costa et al, allows for an unprecedented level of detail to understand cell cycle dynamics during axolotl tissue regeneration, 3,4 particularly in combination with either live imaging or the recently developed optical clearing protocols for salamander systems. [5][6][7][8] Leo Otsuki (IMP, Austria) provided an overview of how these novel imaging tools can be used to study cell cycle kinetics during axolotl spinal cord regeneration.…”
Section: The Wonders Of Regenerationmentioning
confidence: 99%
“…These experiments are key to support comparative developmental studies and identify conserved and divergent regulatory modules controlling axolotl developmental and regenerative programs. So much can be done with these animals, such as gain and loss of function, 8‐10 CRISPR‐mediated transgenesis, 10,11 single‐cell characterization, 12‐16 live imaging, 17‐20 transplants and cell lineage tracing, 20‐27 and the use of ex vivo explants 28 to compare the developmental processes of this unique salamander to the robust body of avian, frog, zebrafish, and mouse developmental research. For example, axolotl gills can regenerate, yet they are one of three modes of respiration at the organism's disposal, and their full role remains unknown 29 …”
Section: Introductionmentioning
confidence: 99%